2021
DOI: 10.3399/bjgpo.2021.0094
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with heart failure with preserved ejection fraction in primary care: a cross-sectional analysis

Abstract: BackgroundMany patients with heart failure with preserved ejection fraction (HFpEF) are undiagnosed, and UK general practice registers do not typically record HF sub-type. Improvements in management of HFpEF is dependent on improved identification and characterisation of patients in primary care.AimsTo describe a cohort of patients recruited from primary care with suspected HFpEF and compare patients in whom HFpEF was confirmed and refuted.Design and SettingBaseline data from a longitudinal cohort study of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Similarly, the short walked distance (6MWD) recorded in the current study (mean 268 m) is somewhat lower than reported within earlier findings (273-318m) [42,43] and may correspond with referral for severity of symptoms. Participants recruited to Wolsk et al [43] and Forsyth et al [42] investigations were considerably older (67-79 years).…”
Section: Baseline Characteristics Of Participantscontrasting
confidence: 57%
“…Similarly, the short walked distance (6MWD) recorded in the current study (mean 268 m) is somewhat lower than reported within earlier findings (273-318m) [42,43] and may correspond with referral for severity of symptoms. Participants recruited to Wolsk et al [43] and Forsyth et al [42] investigations were considerably older (67-79 years).…”
Section: Baseline Characteristics Of Participantscontrasting
confidence: 57%
“…In patients with confirmed HFpEF, pulmonary disease (obstructive or restrictive lung disease; approximately 30%), anemia (approximately 50%), frailty (up to 50%), and atrial fibrillation (approximately 40% at diagnosis) are common . Evaluating patients with dyspnea and HF risk factors for HFpEF, even if they have comorbid conditions, is important because multifactorial dyspnea is common and specific therapy for HFpEF exists.…”
Section: Methodsmentioning
confidence: 99%